Eksplorasi Etnomatematika Pada Masjid Jamik Kota Bengkulu - Desfa Lusiana; Noke Hanif Afriani; Hafizatul Ardy; Wahyu Widada (Universitas Bengkulu, 2019)
The presence of cultural nuances of mathematics (ethnomatematics) will make a major contribution to the learning of mathematics. The purpose of this study is to identify and describe mathematical objects contained in the architecture of Jamik Mosque in Bengkulu City and how they are used in mathematics learning. This research is a qualitative research using ethnographic methods. The instrument in this study was the human instrument, the researcher was directly related to the research and acted as a data collector through library data collection, observation and documentation. Data analysis techniques are performed by data reduction, data presentation and data analysis and data exposure. The results of the study showed that the shape and architecture of Bengkulu City Jamik Mosque has ethnomatematics related to mathematical concepts including triangles, rectangles, circles, cubes, beams, pyramid and tubes. The mathematical concepts found in the Jamik Mosque can be used to introduce and understand the concepts of the geometry concepts through local culture.